0120 Menstrual Cycle-Related Changes in Sleep-Dependent Emotional Memory Consolidation. (25th May 2022) - Zhang, Jing; Simon, Katharine; Shuster, Alessandra; Sattari, Negin; Alzueta, Elisabet; Dulai, Teji; de Zambotti, Massimiliano; Baker, Fiona; Mednick, Sara
Abstract: Introduction: Emotional, more than neutral, experiences are preferentially consolidated during sleep. Fluctuating reproductive hormonal levels across the menstrual cycle are associated with changes in sleep features that are implicated in emotional memory consolidation. Yet, the interaction between menstrual cycle phases, sleep, and emotional memory remains unknown. The current study investigates how sleep-dependent emotional memory consolidation changes across the menstrual cycle in both young and midlife women. Methods: Thirty-one young (MAge=25.32y, SD=5.69y) and 33 midlife (MAge=47.88y, SD=2.86y) women enrolled in the study. Each woman completed four remote visits at different menstrual phases, estimated from self-reports and measured ovulation: menses (low hormone), late-follicular (high estrogen), mid-luteal (high estrogen and progesterone), and late-luteal (falling hormones). During each visit, participants completed the Emotional Picture Task (EPT) via Pavlovia, a web-based testing platform. Participants completed encoding and immediate test in the evening (Test 1) and retested (Test 2) the following morning. During encoding, participants viewed negative and neutral images (selected from the IAPS). During testing, for each image, participants reported if it was old or new, and rated the arousal (low to high) and valence (neutral to negative). We measured dPrime at each test and calculated a difference score for overnight memory improvement. Sleep was recorded using Oura ring, a multi-sensor wearable sleep tracker. Mixed linear models determined the effect of menstrual phase on EPT, with visit as a covariate, and relevant sleep features. Results: Irrespective of age, menstrual cycle phase (p<0.05) predicted overnight dPrime change score for negative images. Specifically, memory improvement was the highest during mid-luteal, while menses showed the most forgetting. In addition, longer time in bed was associated with less forgetting (p<0.01). These effects were not observed for neutral images (ps>0.05). Conclusion: Menstrual phases are characterized by specific sex hormone profiles that can interact with both memory and sleep. The current findings indicate that sleep-dependent memory may also be affected by these changes, specifically memories that have negative emotionally content are more resilient to forgetting during the midluteal phase when both estrogen and progesterone are highest. Future studies (e.g., sleep manipulation) are required to reveal the specific sleep features associated with these effects. Support (If Any): RF1AG061355 (Baker/Mednick)